Some Phrygian Plant and Insect Remains from Kerkenes Dağ, Central Anatolia (Turkey) - Smith, Alexia; Branting, Scott (Ethnobiology Letters, 2014)
During the 1996 and 2000 seasons of excavation at Kerkenes Dağ, a large single‐period Phrygian mountain‐top city located in central Turkey, a small assemblage of archaeobotanical remains and an insect were recovered from two specific archaeological contexts dated to the 540s B.C. This report documents a well‐cleaned Triticum durum/aestivum grain cache retrieved from a baking area, along with hand‐picked remains of Cornus mas, Cerasus cf. avium, and a Brachycerus sp. weevil.